The multifaceted nature of endogenous cardiac regeneration - Rolland, Laura; Jopling, Chris (Frontiers in Cardiovascular Medicine, 2023)
Since the first evidence of cardiac regeneration was observed, almost 50 years ago, more studies have highlighted the endogenous regenerative abilities of several models following cardiac injury. In particular, analysis of cardiac regeneration in zebrafish and neonatal mice has uncovered numerous mechanisms involved in the regenerative process. It is now apparent that cardiac regeneration is not simply achieved by inducing cardiomyocytes to proliferate but requires a multifaceted response involving numerous different cell types, signaling pathways and mechanisms which must all work in harmony in order for regeneration to occur. In this review we will endeavor to highlight a variety of processes that have been identifed as being essential for cardiac regeneration.